PREVALENCE OF HEARING IMPAIRMENT AMONG HIGH RISK NEONATES (Journal of Pharmaceutical Negative Results, 2022)
Programmes that focus on detecting hearing disabilities at an early age of child help in improving the overall development of the child in cognitive, motor and social domains.4 With the development and advances in technology and expertise occurring in neonatology in our country, many high risk new borns are saved but unfortunately they are saved with hearing impairment. This hearing impairment would need detection at earliest possible time to minimize its impact on cognition, language, communication and education.